Process strategies in operation management - Sulong @ A. Rashid, Ruzaidah; Ali, Noor Malinjasari; Mohd Noor, Hasmida; Hamzah, Siti Fatimah Mardiah; Mat Salleh, Suzila; Mohamed Nor, Raslina (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
A process strategy is an organization's approach to transform resources into goods and services (Heizer, Render & Munson, 2020). Process strategy is critical to a company because the selected process will have a long-term effect on cost, the flexibility of production and quality of goods produced. There are four (4) approaches to transform input into valuable output: product focus, process focus, repetitive focus, and mass customization. Types of Process Strategy